2020
DOI: 10.3390/nu12123631
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Gnetin C in Prostate Cancer: A Pre-Clinical Study

Abstract: Natural stilbenes have gained significant attention in the scientific community owing to their potential anticancer effects against prostate cancer. We recently reported that Gnetin C, a resveratrol (Res) dimer, demonstrated more potent inhibition of metastasis-associated protein 1/v-ets avian erythroblastosis virus E26 oncogene homolog 2 (MTA1/ETS2) axis in prostate cancer cell lines than other stilbenes. In this study, we investigated in vivo antitumor effects of Gnetin C in two doses (50 and 25 mg/kg, i.p.)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 49 publications
1
30
0
Order By: Relevance
“…The inhibitory effects of resveratrol and pterostilbene on MTA1-mediated angiogenesis involving HIF-1a, VEGF, and IL-1β were also consistently reported (Kai et al, 2011;Li et al, 2013;Dhar et al, 2016;Butt et al, 2017;Hemani et al, 2022). We have also shown the MTA1-mediated and MTA1 independent chemopreventive and therapeutic value of Gnetin C in prostate cancer in vitro and in vivo (Kumar et al, 2019;Gadkari et al, 2020). Importantly, stilbenes can inhibit MTA1-associated oncogenic miRNAs (Figure 3).…”
Section: Stilbenes As Inhibitors Of Mta1 Signaling and Associated Mir...supporting
confidence: 79%
See 2 more Smart Citations
“…The inhibitory effects of resveratrol and pterostilbene on MTA1-mediated angiogenesis involving HIF-1a, VEGF, and IL-1β were also consistently reported (Kai et al, 2011;Li et al, 2013;Dhar et al, 2016;Butt et al, 2017;Hemani et al, 2022). We have also shown the MTA1-mediated and MTA1 independent chemopreventive and therapeutic value of Gnetin C in prostate cancer in vitro and in vivo (Kumar et al, 2019;Gadkari et al, 2020). Importantly, stilbenes can inhibit MTA1-associated oncogenic miRNAs (Figure 3).…”
Section: Stilbenes As Inhibitors Of Mta1 Signaling and Associated Mir...supporting
confidence: 79%
“…Nutritional interception in intermediate- and high-risk active surveillance patients should target specific molecular pathways. Particularly, our group has shown that natural dietary stilbenes exhibit targeted chemoprotective, interceptive and therapeutic effects against prostate cancer in vitro and in vivo ( Kai et al, 2010 ; Li et al, 2013 ; Dhar et al, 2016 ; Butt et al, 2017 ; Kumar et al, 2019 ; Gadkari et al, 2020 ; Levenson, 2020 ; Hemani et al, 2022 ). This review will focus on the potential of natural stilbenes to protect against prostate cancer through the modulation of specific miRNAs that can conceivably be detected in bloodstream and urine and serve as prognostic and predictive biomarkers for certain populations of prostate cancer patients in the future.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently reported that a pterostilbene-supplemented diet exerted beneficial effects by diminishing inflammatory pathways and accelerated PIN progression in R26 MTA1 ; Pten +/f mice [ 27 ]. Since we have also previously demonstrated the more potent MTA1-targeted inhibitory activity of gnetin C, a dimer resveratrol ( Figure 1 A), compared to resveratrol and pterostilbene, both in vitro and in prostate cancer xenografts [ 31 , 35 ], we sought to determine the efficacy of gnetin C in an adequate preclinical model of prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, MTA1 is gradually perceived to be a new target candidate for cancer drug treatment. Recently, MTA1-targeted chemopreventive agents for cancer therapy have been continuously developed and studied [175][176][177]. For instance, natural compound resveratrol and its analog pterostilbene have been recognized as the potent inhibitors for MTA1 and MTA1-guided signaling [178][179][180].…”
Section: Therapeutic Significance Of Mta1mentioning
confidence: 99%